Análise da viabilidade técnica e ambiental de vias cicláveis na cidade de Presidente Epitácio-SP - Freitas, Verônica de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research develops an analysis of the technical and environmental feasibility of cycle routes in the Tourist Office of Presidente Epitácio, State of São Paulo, to contribute to the planners in the management of the transport system. Therefore, the research based in the literature review with emphasis on passenger transport system with a non-motorized bicycle technology type. Subsequently, it was determined by the statistical method, Simple Random Sampling, the sample was representative for questionnaires. These were important for the study of matrices Origin-Destination (O/D), to know the displacement of people, their main routes, how, when, for what purpose, indicating the intention to leisure, sports practice or utilitarian purposes. Thus, it was possible to tabulate the data and plotting arrays in Google Maps software. The results demonstrated the technical and environmental feasibility of cycling in urbe, in which it outlined the main cycling demands. Thus it is believed that this work will help when planning the city, always emphasizing the ecological, sustainable urban mobility, urban layout and topography, mainly indicate the location of bike lanes on city roads. Therefore, the reason of this work is to encourage the use of bicycles, emphasizing the implementation of cycling infrastructure to maintain and bring in new fans, as the socioeconomic and physical and functional characteristics of the city .And so, trying to subvert the current logic that prioritizes the automobile on pedestrians, cyclists and public transport. The main desire of this work is to obtain a healthy city, because the current transport sector of the country has problems of environmental, social and energy unsustainability, while the bike has numerous benefits for the environment, health and cyclist economy. It is believed that these measures will promote the reduction of accident rates, provide personal security to the rider and his bike, improve the ...

Nesta pesquisa desenvolve-se uma análise da viabilidade técnica e ambiental de vias cicláveis na Estância Turística de Presidente Epitácio, Estado de São Paulo, para contribuir com os planejadores na gestão do sistema de transporte. Para tanto, a pesquisa embasou-se na revisão bibliográfica com ênfase no sistema de transporte de passageiros com a tecnologia não motorizada do tipo bicicleta. Posteriormente, determinou-se por meio do método estatístico, Amostragem Aleatória Simples, a amostra com representatividade para aplicação de questionários. Estes foram importantes para o estudo das matrizes origem e destino (O/D), para saber o deslocamento das pessoas, suas principais rotas, como, quando, por qual motivo, ou seja, indicando a intenção de lazer, de prática esportiva ou fins utilitários. Assim, foi possível tabular os dados e traçar as matrizes no software Google Maps. Os resultados obtidos comprovaram a viabilidade técnica e ambiental do uso da bicicleta na urbe, na qual se traçaram as principais demandas cicloviárias. Assim acredita-se que este trabalho irá contribuir no momento de planejar a cidade, sempre ressaltando os aspectos ambientais, mobilidade urbana sustentável, traçado e topografia urbana, principalmente por indicar a localização das vias cicláveis na cidade. Por conseguinte, a razão deste trabalho vem a estimular o uso da bicicleta, valorizando a implantação da infraestrutura cicloviária para manter e trazer novos adeptos, conforme as características socioeconômicas e físíco-funcionais da urbe. Assim, o objetivo é tentar, subverter a lógica atual, que prioriza o automóvel sobre os pedestres, os ciclistas e o transporte público. O principal anseio deste trabalho é de se obter uma cidade saudável, pois o setor de transportes atual do país tem problemas de insustentabilidade ambiental, social e energética, enquanto que a bicicleta apresenta inúmeros benefícios para o meio ambiente, ...
Keywords: Ciclovias - Presidente Epitácio (SP); Bicicletas; Infra-estrutura (Economia); Transportes - Transito de passageiros; Desenvolvimento sustentável; Infrastructure (Economics)